Evaluation of a Modified Hybrid‐Maize Model Incorporating a Newly Developed Module of Plastic Film Mulching. Issue 6 (1st November 2014) - Hou, Peng; Cui, Zhenling; Bu, Lingduo; Yang, Haishun; Zhang, Fusuo; Li, Shaokun
ABSTRACT: Understanding maize ( Zea mays L.) growth, development, and production under plastic film mulching is useful to improve crop management strategies and increase grain yield in areas with limited water and low temperatures. A new plastic film mulching module for the Hybrid‐Maize model was developed to simulate maize development and grain yield. This paper evaluates the performance of the new model at Changwu experimental station, northwest China, and at the 852 farm and Qixing farm in northeast China, compared with the original Hybrid‐Maize model. Compared with measured data, the root mean square error (RMSE) and normalized root mean square error (NRMSE) values for leaf area index (LAI) were 1.0 and 29% for the original model and 0.72 and 20% for the modified model, respectively. The RMSE and NRMSE values for the aboveground dry matter simulated by the original model were 2674 kg ha −1 and 24% compared with 1552 kg ha −1 and 14% by the new model. The RMSE and NRMSE values for the grain dry matter were 495 kg ha −1 and 5.5% by the original model and 441 kg ha −1 and 4.9% by the modified model. The RMSE and NRMSE values for the LAI and aboveground and grain dry matter were all lower for the modified model, indicating improved simulations. With the modified model, simulated aboveground dry matter and LAI increased >14 and 30%, respectively, compared with the original model. However, the modified model overestimated LAI and aboveground dry matter in the maize vegetative stage.